Evaluation of AGO Adsorption Rate Isotherms Using Adsorbent Formulation of Plantain Agbagba1 and Clay of Different Mix Ratio in Pollutant Remediation in Salt Water - Nnadi Vincent Gilbert; Ukpaka Chukwuemeka Peter (International Journal of Pollution: Prevention & Control, 2024)
The application of some agro-based materials in combination with day soil, for the production of adsorbents were investigated in relationship to their performance in AGO (Diesel) treatment in a batch process unit. The research allows the model concept of Langmuir isotherm, Frundlich isotherm and Temkin Isotherm for the determination of the adsorption rate of the various isotherms with respect to the effect of the particle size and the mixed ratios of the clay soil and the agro-based materials used in this research. The particle size investigated were 1.18 mm, 50 and the performance of the adsorbent was rated with the particle size as observed on the obtained data. The characteristics of AGO adsorbed with respect to the quantum rate of adsorption shows that the smaller the particle size the more the rate of contaminants removal will increase. Mixed ratios the day soil to the agro-based materials used were R1:9, R:2:8, R3.7, R4:6, R5:5, R6:4, R8:4 and the isotherms value determine by establishing the regression linear lien of the plots. The process allows the evaluation of the slope and intercepts values, which was subjected to the formulated isotherm models of Temkins, Freudlich and Largmuir. The adsorbents were produced by using clay soil mixed with each of the agro – based materials of plantain agbagba. The research revealed that the adsorption rate of the output response increases with increase in the dependent parameter of plot in the x-coordinate and this behaviour was experienced in all the plot showing the significance of the produced adsorbent as a good formulation for treatment of AGO (diesel product) in salt water medium.
Keywords: AgO; Medium; Salt; adsorption; contaminants; treatment; water